Impact of voluntary exercise and housing conditions on hippocampal glucocorticoid receptor, miR-124 and anxiety - Pan-Vazquez, Alejandro; Rye, Natasha; Ameri, Mitra; McSparron, Bethan; Smallwood, Gabriella; Bickerdyke, Jordan; Rathbone, Alex; Dajas-Bailador, Federico; Toledo-Rodriguez, Maria (BioMed Central, 2015)
Background: Lack of physical activity and increased levels of stress contribute to the development of multiple physical and mental disorders. An increasing number of studies relate voluntary exercise with greater resilience to psychological stress, a process that is highly regulated by the hypothalamic-pituitary-adrenal (HPA) axis. However, the molecular mechanisms underlying the beneficial effects of exercise on stress resilience are still poorly understood. Here we have studied the impact of long term exercise and housing conditions on: a) hippocampal expression of glucocorticoid receptor (Nr3c1), b) epigenetic regulation of Nr3c1 (DNA methylation at the Nr3c1-1F promoter and miR-124 expression), c) anxiety (elevated plus maze, EPM), and d) adrenal gland weight and adrenocorticotropic hormone receptor (Mc2r) expression. Results: Exercise increased Nr3c1 and Nr3c1-1F expression and decreased miR-124 levels in the hippocampus in single-housed mice, suggesting enhanced resilience to stress. The opposite was found for pair-housed animals. Bisulfite sequencing showed virtually no DNA methylation in the Nr3c1-1F promoter region. Single-housing increased the time spent on stretch attend postures. Exercise decreased the time spent at the open arms of the EPM, however, the mobility of the exercise groups was significantly lower. Exercise had opposite effects on the adrenal gland weight of single and pair-housed mice, while it had no effect on adrenal Mc2r expression. Conclusions: These results suggest that exercise exerts a positive impact on stress resilience in single-housed mice that could be mediated by decreasing miR-124 and increasing Nr3c1 expression in the hippocampus. However, pair-housing reverses these effects possibly due to stress from dominance disputes between pairs.